Characterization of Lomer junctions based on the Lomer arm length distribution in dislocation networks. (15th March 2023) - Katzer, Balduin; Zoller, Kolja; Bermuth, Julia; Weygand, Daniel; Schulz, Katrin
Abstract: During the plastic deformation of crystalline materials, 3d dislocation networks form based on dislocation junctions. Particularly, immobile Lomer junctions are essential for the stability of dislocation networks. However, the formed Lomer junctions can unzip and dissolve again, if the linked mobile dislocations of the Lomer junction - the Lomer arms - experience sufficiently high resolved shear stresses. To generate a better understanding of the dislocation network stability and to pave the way to a general stability criterion of dislocation networks, we investigate the Lomer arm length distribution in dislocation networks by analyzing discrete dislocation dynamics simulation data of tensile-tested aluminum single crystals. We show that an exponential distribution fits best to the Lomer arm length distribution in the systems considered, which is independent of the crystal orientation. The influence of the slip system activity on the Lomer arm length distribution is discussed. Graphical abstract: